The Intrinsic Analysis of Narrative and Visual Elements in Uketsu’s Strange Pictures - Rosalyn Magdalena Br Sitorus; Muhammad Fakhran al Ramadhan (Lakon : Jurnal Kajian Sastra dan Budaya, 2026)
The growing popularity of translated Japanese literature among Indonesian readers reflects a broader movement of multimodal storytelling and digital reader interaction. This research examines at the way narrative structures and visual aspects create suspense and thematic coherence in Uketsu's Strange Pictures. This research utilizes an intrinsic qualitative method based on Barthes' structuralism and Genette's narratology to investigate how textual and visual cues work together to form meaning. This study examines how the novel's use of time, focalization, and symbolic imagery generates tension while transforming readers into active interpreters. The findings demonstrate that Uketsu's hybrid narrative design combines verbal and visual systems into a continuous semiotic framework, with images contributing not as illustrations but as crucial narrative components.